Callochiton : Gray 1847 ... - Dell'Angelo, Bruno; Schwabe, Enrico; Gori, Sandro; Sosso, Maurizio; Bonfitto, Antonio (Zenodo, 2014)
Genus Callochiton Gray, 1847 Callochiton : Gray 1847 a : 126. Type species: Chiton laevis Montagu, 1803 ( non Pennant, 1777) [= Callochiton septemvalvis (Montagu, 1803), fide Kaas 1978], by subsequent designation (Gray 1847 b : 168). For synonymy, see Kaas & Van Belle (1985 b ). Distribution: Mostly tropical and subtropical regions of the Indo-Pacific (including Japan; absent from the northeastern Pacific). In the Atlantic Ocean, restricted to the eastern and southern (sub-Antarctic) parts. Oligocene – Recent. ... : Published as part of Dell'Angelo, Bruno, Schwabe, Enrico, Gori, Sandro, Sosso, Maurizio & Bonfitto, Antonio, 2014, Chitons (Mollusca, Polyplacophora) from São Tomé and Príncipe Islands, pp. 171-200 in African Invertebrates 55 (2) on page 181, DOI: 10.5281/zenodo.7680891 ...